Qur'anic perspective of gender equality: Classical and modern tafsir - Alfani, Ilzam Hubby Dzikrillah; Mukhsin, Mukhsin; Khusnadin, Muhammad Hafidz; Chodijah, Siti; Luthfia, Asya Dwina (Universitas Islam Negeri Ar-Raniry, 2025)
Qur’anic interpretation of gender equality has become an increasingly significant topic in contemporary Islamic studies, especially in the context of changing social dynamics. This article aims to analyse the different interpretations of Qur’anic verses relating to gender equality through a comparative approach between classical and modern tafsir. The study employs qualitative approach with library research method. Through this study, the author explores how classical tafsir, which is often influenced by the cultural and social norms of its time, interacts with modern tafsir that focuses more on the principles of social justice and women's rights. The classical exegeses include Tafsir al-Tabari (Ibnu Jarir al-Tabari), Tafsir al-Qurtubi (by Al-Imam Abu Abdillah Muhammad), and Tafsir Ibnu Kathir (by Imam Ibn Kathir). Meanwhile, modern exegeses include Tafsir al-Misbah (by Quraish Shihab), Tafsir al-Maraghi (by Imam Ahmad Musthafa Al-Maraghi), as well as the works of Asma Barlas and Fazlur Rahman. The article highlights the different approaches in interpreting verses such as Q.S. An-Nisa' and Al-Baqarah relating to gender roles, women's rights in marriage, and social participation. The findings of this study indicate a significant paradigm shift in modern tafsir that is more inclusive and responsive to gender issues in society, without leaving the foundation of Islamic principles. This research also offers a critical reflection on the relevance of Qur’anic interpretation in supporting gender equality in the contemporary era, as well as the challenges faced in trying to bridge classical and modern interpretations.